Human Physiology During Exposure to the Cave Environment: A Systematic Review With Implications for Aerospace Medicine - Zuccarelli, Lucrezia; Galasso, Letizia; Turner, Rachel; Coffey, Emily J. B.; Bessone, Loredana; Strapazzon, Giacomo (Frontiers in Physiology, 2019)
Background: Successful long-duration missions outside low-Earth orbit will depend on technical and physiological challenges under abnormal environmental conditions. Caves, characterized by absence of light, confinement, three-dimensional human movement and long-duration isolation, are identifiably one of the earliest examples of scientific enquiry into space analogs. However, little is known about the holistic human physiological response during cave exploration or prolonged habitation. Objectives: The aim of our review was to conduct a systematic bibliographic research review of the effects of short and prolonged exposure to a cave environment on human physiology, with a view to extend the results to implications for human planetary exploration missions. Methods: A systematic search was conducted following the structured PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines for electronic databases. Results: The search retrieved 1,519 studies. There were 50 articles selected for further consideration, of which 31 met our inclusion criteria. Short-term cave exposure studies have investigated visual dysfunction, cardiovascular, endocrine-metabolic, immunologic-hematological and muscular responses in humans. Augmentations of heart rate, muscular damage, initial anticipatory stress reaction and inflammatory responses were reported during caving activity. Prolonged exposure studies mainly investigated whether biological rhythms persist or desist in the absence of standard environmental conditions. Changes were evident in estimated vs. actual rest-activity cycle periods and external desynchronization, body temperature, performance reaction time and heart rate cycles. All studies have shown a marked methodological heterogeneity and lack reproduction under controlled conditions. Conclusions: This review facilitates a further comparison of the proposed physiological impact of a subterranean space analog environment, with existing knowledge in related disciplines pertaining to human operative preparation under challenging environmental conditions. This comprehensive overview should stimulate more reproducible research on this topic and offer the opportunity to advance study design and focus future human research in the cave environment on noteworthy, reproducible projects.